Control of the pore size of honeycomb polymer film from micrometers to nanometers via substrate-temperature regulation and its application to photovoltaic and heat-resistant polymer films. (8th October 2019) - Zheng, Yanqiong; Tang, Jie; Li, Weiguang; Yu, Junle; Bin Wei,; Li, Xifeng; Shi, Jifeng; Miyazaki, Koji
Abstract: Honeycomb porous polystyrene (PS) films with an aspect ratio of pore depth to pore diameter at approximately 1.0 were fabricated using the breath figure (BF) method. Two modes of water droplet coalescence in the pore growth were observed in real-time by optical microscopy. Pore size significantly increases with the increase in humidity and the decrease in substrate temperature. The porous pattern could emerge even at room temperature under high humidity of 80%. Boiling point and solvent density significantly influence the pore distribution and pore depth. Chloroform and tetrahydrofuran achieve more uniform hexagonal patterns than benzene and dichloromethane. Subsequently, to obtain nanometer porous PS film, the fast-evaporation BF process was designed by regulating the gradient substrate temperature and evaporation time, and porous mesoscopic PS film was obtained. The minimum pore diameter and corresponding pore depth are about 120 nm and 27 nm, respectively. Finally, the fast-evaporation BF process was applied to the honeycomb film formation of photovoltaic polymer poly(3-hexylthiophene) (P3HT), and the heat-resistant polymers polysulfone (PSF) and polyimide (PI).